2017
DOI: 10.3899/jrheum.160340
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Disease Characteristics, Organ Damage, and Survival in Patients with Juvenile-onset and Adult-onset Systemic Lupus Erythematosus in a Combined Cohort from 2 Tertiary Centers in Turkey

Abstract: We report a higher frequency in the jSLE group of renal involvement, cutaneous symptoms, oral ulcers, NP manifestations, AIHA, and anti-dsDNA positivity. A significant proportion of patients in the jSLE group had damage, most prominently in the renal domain. Our findings might support different genetic/environmental backgrounds for these 2 subgroups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
44
1
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 44 publications
7
44
1
1
Order By: Relevance
“…In the present study, 17% of the patients were grouped into a cluster with prevalent renal (55.4%) and ocular damage (58.0%), which resembled cluster 2 of the juvenile SLE study (14.5% of total patients, 60% with renal damage, 54.0% with ocular damage), while Pego‐Reigosa et al identified no damage cluster with frequent renal damage among the adult patients with SLE. The presence of a renal damage cluster may be associated with the age or ethnic background of the included patients, as renal damage is significantly more frequent in Asian patients than Western patients and in juvenile‐onset SLE than in adult‐onset SLE …”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 17% of the patients were grouped into a cluster with prevalent renal (55.4%) and ocular damage (58.0%), which resembled cluster 2 of the juvenile SLE study (14.5% of total patients, 60% with renal damage, 54.0% with ocular damage), while Pego‐Reigosa et al identified no damage cluster with frequent renal damage among the adult patients with SLE. The presence of a renal damage cluster may be associated with the age or ethnic background of the included patients, as renal damage is significantly more frequent in Asian patients than Western patients and in juvenile‐onset SLE than in adult‐onset SLE …”
Section: Discussionmentioning
confidence: 99%
“…Accumulating disease damage from CLE correlates inversely with age of disease onset, producing physical and psychological implications during a formative time in development. In addition, paediatric‐onset SLE differs significantly from adult‐onset SLE, with a greater frequency of end‐organ damage including renal involvement at presentation, a requirement for sustained immunosuppression, and higher overall mortality . The validation of this tool in paediatric CLE will facilitate approval of much‐needed paediatric lupus treatments and help to standardize patient care …”
Section: Discussionmentioning
confidence: 99%
“…Among all SLE patients, 15-20% have a disease onset in childhood namely juvenile SLE (jSLE) 3 . Disease severity and outcome of jSLE patients are more severe than adult onset SLE due to the higher frequency of central nervous system and renal involvement; requiring more intense immunosuppressive treatments 4 . In the past two decades, with achieving early diagnosis and improved treatment modalities, jSLE patients might live longer with a chronic disease.…”
Section: Introductionmentioning
confidence: 99%